Rapid and Visual Detection of SARS-CoV-2 RNA Based on Reverse Transcription-Recombinase Polymerase Amplification with Closed Vertical Flow Visualization Strip Assay - Yumeng Song; Pei Huang; Mengtao Yu; Yuanguo Li; Hongli Jin; Jiazhang Qiu; Yuanyuan Li; Yuwei Gao; Haili Zhang; Hualei Wang (Microbiology Spectrum, 2023)
ABSTRACT Coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was initially identified in 2019, after which it spread rapidly throughout the world. With the progression of the epidemic, new variants of SARS-CoV-2 with faster transmission speeds and higher infectivity have constantly emerged. The proportions of people asymptomatically infected or reinfected after vaccination have increased correspondingly, making the prevention and control of COVID-19 extremely difficult. There is therefore an urgent need for rapid, convenient, and inexpensive detection methods. In this paper, we established a nucleic acid visualization assay targeting the SARS-CoV-2 nucleoprotein (N) gene by combining reverse transcription-recombinase polymerase amplification with closed vertical flow visualization strip (RT-RPA-VF). This method had high sensitivity, comparable to that of reverse transcription-quantitative PCR (RT-qPCR), and the concordance between RT-RPA-VF and RT-qPCR methods was 100%. This detection method is highly specific and is not compatible with bat coronavirus HKU4, human coronaviruses 229E, OC43, and HKU1-CoV, Middle East respiratory syndrome coronavirus (MERS-CoV), or other respiratory pathogens. However, multiple SARS-CoV-2 variants are detectable within 25 min at 42°C using this visual method, including RNA transcripts of the Wuhan-Hu-1 strain at levels as low as 1 copy/μL, the Delta strain at 1 copy/μL, and the Omicron strain at 0.77 copies/μL. The RT-RPA-VF method is a simple operation for the rapid diagnosis of COVID-19 that is safe and free from aerosol contamination and could be an affordable and attractive choice for governments seeking to promote their emergency preparedness and better their responses to the continuing COVID-19 epidemic. In addition, this method also has great potential for early monitoring and warning of the epidemic situation at on-site-nursing points. IMPORTANCE The global COVID-19 epidemic, ongoing since the initial outbreak in 2019, has caused panic and huge economic losses worldwide. Due to the continuous emergence of new variants, COVID-19 has been responsible for a higher proportion of asymptomatic patients than the previously identified SARS and MERS, which makes early diagnosis and prevention more difficult. In this manuscript, we describe a rapid, sensitive, and specific detection tool, RT-RPA-VF. This tool provides a new alternative for the detection of SARS-CoV-2 variants in a range as low as 1 to 0.77 copies/μL RNA transcripts. RT-RPA-VF has great potential to ease the pressure of medical diagnosis and the accurate identification of patients with suspected COVID-19 at point-of-care.